2019
DOI: 10.3389/fpsyt.2019.00832
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis E in a Patient Cohort Presenting With Addictive Injection Behavior

Abstract: Introduction: Hepatitis E is the most common cause of acute viral hepatitis worldwide. Seroprevalence is approximately 15% in developed countries, and 22% in France. hepatitis E virus (HEV) can be transmitted via transfusions and therefore possibly intravenous (IV) drug use. Hepatitis E serology is routinely tested in patients who seek medical advice for addictive injection behavior at the addiction treatment, support and prevention unit of Toulouse University Hospital. We assume that hepatitis E is more preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Studies of HEV PCR positivity rates of blood donors worldwide [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]; Table S2. Studies of HEV seroprevalence of blood donors worldwide [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70...…”
unclassified
“…Studies of HEV PCR positivity rates of blood donors worldwide [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]; Table S2. Studies of HEV seroprevalence of blood donors worldwide [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70...…”
unclassified
“…However, the control populations in most studies were unmatched to the PWID groups, even for age, which is a major determinant of HEV seropositivity [ 30 , 31 ]. Only one study included an age- and sex-matched control population [ 13 ]. However, a limitation of this study was its small sample size of only 52 PWIDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of addictive injection behavior as a risk factor for hepatitis E is uncertain. HEV IgG seroprevalence among PWIDs in Europe and North America ranges from 2.8–62% [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Comparisons of the HEV seroprevalence between PWIDs and non-drug-using control groups have produced conflicting results; some studies have found significant differences [ 18 , 19 , 21 ], while others have concluded that PWIDs are not at increased risk of hepatitis E [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation